Business philosophy during digital transformation in wartime conditions. The case of Ukraine in critical perspective - Yaroslav Pushak; Nataliia Trushkina; Vitaliy Flyak; Iryna Bezpalko (Clío)
Companies are not only organizations pursuing profit, but they are also a key economic agent that, in different contexts, must provide society with basic goods and services to satisfy its needs. In the case of Ukraine, the war situation happened since February 2022 makes the situation of domestic enterprises difficult, as they must now adapt to the requirements of a war economy. Using the method of the history of ideas, the aim of the research was to describe the meaning of business philosophy during the digital transformation in conditions of war in Ukraine, which involved a critical thinking exercise that tried to answer the question Is there a general business philosophy in Ukraine that, beyond the particularities of each business, represents the being and doing of entrepreneurs in the process of digital transformation and in the context of war? The obtained results allow concluding that, no philosophy develops in an ethereal dimension, isolated from the dialectical forces and contradictions of its time, therefore, every business philosophy constitutes a space where the social representations of a given time and space converge.